PRODUCTION AND DEVELOPMENT OF FERTIGATED COFFEE PLANTS IN WESTERN REGION OF BAHIA - Vicente, Marcelo Rossi; Mantovani, Everardo Chartuni; Fernandes, André Luis Teixeira; Neves, Julio Cesar Lima; Dias, Santos Henrique Brant; Figueredo, Edmilson Marques (Coffee Science - ISSN 1984-3909, 2018)
This work was to evaluate the effects of different doses and fertigation parceling on the production and development of irrigated coffee drip in the Western Bahia region. He carried out the work on the farm White River Café, located in Barreiras - BA in coffee adults, approximately 3.5 years of age, Catuaí IAC 144. The experiment was conducted in a factorial 3 x 3, three levels of nitrogen and potassium fertilization (900/800, 600/500 and 300/250 kg ha-1 yr-1 N and K2O) in 3 monthly installments of fertigation (2, 4 and 8 times). The variables in the experiment were: productivity, growth, yield and sieve. The doses of 600/500 and 900/800 kg ha-1 yr-1 N / K2O, the highest yield of the coffee. The installments of fertigation at two and eight times per month were higher in productivity. A higher effect of splitting the fertigation, on the effect of N and K2O in the coffee development variables (crown diameter and plant height). There was no effect of dose and fertigation parceling on rating sieve of coffee beans.